How does consumer engagement evolve when brands post across multiple social media? - Unnava, Vasu; Aravindakshan, Ashwin (Journal of the Academy of Marketing Science, 2021)
Brands allocate their social media advertising across multiple platforms such as Facebook, Twitter, Instagram, and YouTube. Because consumers use multiple social media, brand communications on one platform could generate engagement within the same platform (direct effects) and potentially impact engagement with the brand on the other platforms (spillover effects). Additionally, past engagement with a post on a platform could sustain into the future, thereby improving the longevity of posts (carryover effects). These effects could also vary across platforms. Drawing on recent advertising literature, the authors propose and test differential carryover, spillover, and direct effects within and across social media. The empirical analysis indicates that these effects exist and are significant, supporting the propositions presented. The analysis provides generalizable guidelines to social media marketers on the effectiveness of the various platforms at sustaining a post and at creating direct and spillover effects across other platforms. Finally, the study also exemplifies a resource allocation model for brands to use when allocating their efforts across the various social media platforms to maximize both consumer engagement and the firm’s return on social media investment.